2015
DOI: 10.1097/hjh.0000000000000654
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for local arterial stiffness. Part A

Abstract: We estimated age and sex-specific percentiles of carotid stiffness in a healthy population and assessed the association between cardiovascular risk factors and carotid distensibility coefficient Z-scores, which enables comparison of carotid stiffness values between (patient) groups with different cardiovascular risk profiles, helping interpretation of such measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 46 publications
(63 reference statements)
3
88
2
1
Order By: Relevance
“…The practical relevance of our findings becomes evident when considering the reference values for carotid artery distensibility [3]. Engelen et al showed that the difference in carotid distension between the healthy subpopulation and the subpopulation with prior cardiovascular disease is about 0.10 mm.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The practical relevance of our findings becomes evident when considering the reference values for carotid artery distensibility [3]. Engelen et al showed that the difference in carotid distension between the healthy subpopulation and the subpopulation with prior cardiovascular disease is about 0.10 mm.…”
Section: Discussionmentioning
confidence: 57%
“…In this subgroup, distension in study participants with at least one cardiovascular risk factor (i.e. smoking and self-reported diabetes) was found to be 0.05 mm smaller than in study participants without risk factors [3].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These patients showed a 13% improvement in both PWV and carotid stiffness, 6% increase in ICD, 7% increase in IMT, and a 17% reduction in CWS. These changes are important since they correspond grossly to 10/15 years of normal vascular aging 23, 24, 25. This improvement persisted unchanged after adjustment for dialysis duration and other potential confounders.…”
Section: Discussionmentioning
confidence: 82%
“…Three measurements were made and the mean value was calculated. For local carotid and femoral distensibility, normal and reference values were recently published but reference values for aortic stiffness were not available (30,31). Generally, these parameters used in clinical studies were compared with those in the controls.…”
Section: Measurement Of Aortic Stiffness Parameters With Echocardiogrmentioning
confidence: 99%